2010
DOI: 10.3109/02656736.2010.485594
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hot-tub therapy on serum Hsp70 level and its benefit on diabetic rats: A preliminary report

Abstract: A decrease in complications in diabetic rats after hot-tub therapy is shown here. An increase in the extracellular Hsp70 level due to HTT was observed. This increase may serve to protect the structure of proteins (e.g. preventing AGE formation), and the observed beneficial effects may be related to it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…9 The influence of thermal therapy on glycemic regulation and metabolic disease has primarily been investigated using rodent models. 17,18,[25][26][27] . However, there are human data to suggest that local heating at the site of insulin infusion improves postprandial insulin action 28,29 and may benefit long-term glycemic control 29,30 and cardiovascular health in humans.…”
Section: Introductionmentioning
confidence: 99%
“…9 The influence of thermal therapy on glycemic regulation and metabolic disease has primarily been investigated using rodent models. 17,18,[25][26][27] . However, there are human data to suggest that local heating at the site of insulin infusion improves postprandial insulin action 28,29 and may benefit long-term glycemic control 29,30 and cardiovascular health in humans.…”
Section: Introductionmentioning
confidence: 99%
“…These results could be related to the promising effect of sauna therapy for patients with diabetes and other life-style diseases [61], as well as with the helpful hottub therapy for diabetic patients [62] and diabetic rats [63]. Moreover, Kokura et al [7] found that whole body hyperthermia (WBH) may provide a new therapeutic or preventive modality against obesity-related diseases such as type 2 diabetes mellitus and metabolic or insulin resistance syndrome [8].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, not all studies have found low iHsps in diabetes (Ugurlucan et al 2010). Not infrequently, these studies were in drug-induced, streptozotocin, diabetes, and the acute stress of the sudden diabetic state could raise the levels initially and with time fall to lower levels (Bathaie et al 2010). Low levels of iHsps contribute to an impaired stress response in a disease disrupted by protein glycation and oxidation, free radical formation, protein aggregation, and inflammation, and may be a clue to the etiology of the disease itself for it sets up for disruption of homeostasis and induction of pathology.…”
Section: Hsp Levels In Diabetesmentioning
confidence: 99%
“…Moreover, diabetics have a decreased amount of slow twitch fibers and correlated to the severity of insulin resistance (Stuart et al 2013). Further debilitating the function of Hsp70 is its glycation, which blocks its protein refolding ability (Bathaie et al 2010). Loss of insulin signaling itself promotes deactivation of HSF1 via an inhibitory phosphorylation of HSF1 by glycogen synthase kinase 3-β (GSK-3β).…”
Section: Hsp Levels In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation